1991
DOI: 10.1128/cmr.4.3.396-.1991
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes CAMP reaction.

Abstract: Listeria monocytogenes CAMP Reaction We would like to clarify a discrepancy on page 170 of the article by Schuchat et al. (2). Table 1 indicates that Listeria monocytogenes gives a positive or negative CAMP (hemolysis enhancement) reaction with Rhodococcus equi. In the discussion of the CAMP reaction, we stated that L. monocytogenes gives a negative CAMP reaction with R. equi. The data reported in Table 1 are adapted from a chapter authored by R. E. Weaver in a laboratory manual available from the Centers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…equui. Schuchat et al (1991) have apparently attributed this to the failure of Coryne. equi strains to produce the appropriate synergistic factor(s), and have emphasized the use of reference strains of Coryne.…”
mentioning
confidence: 99%
“…equui. Schuchat et al (1991) have apparently attributed this to the failure of Coryne. equi strains to produce the appropriate synergistic factor(s), and have emphasized the use of reference strains of Coryne.…”
mentioning
confidence: 99%
“…As highlighted by a Letter to the Editor recently published in Clinical Microbiology Reviews (8), there is controversy over reported results of the CAMP reaction of Listeria monocytogenes with Rhodococcus equi.…”
mentioning
confidence: 99%